2000
DOI: 10.1562/0031-8655(2000)071<0355:potpat>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Participation of the Photosensitizer Alpha-terthienyl in thePeroxidase-catalyzed Oxidation of Indole-3-acetic acid†

Abstract: The plant photosensitizer alpha-terthienyl (alpha T) is toxic toward a variety of organisms, and normally requires exposure to ultraviolet-A radiation for activation and singlet molecular oxygen formation. However, some toxicity has also been reported to occur in the dark. One hypothesis that has been proposed to account for this light-independent toxicity is that the sensitizer becomes activated by energy transfer from the excited-state products of enzymatic reactions. We have investigated this hypothesis usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The marigold polythienyls are only weakly nematicidal when incorporated into soil and require light or the action of peroxidase or other activators to release the singlet oxygen that kills nematodes (49,50). The details of the specific activators and processes involved in the insecticidal, nematicidal, or other toxic activities of these compounds continue to be examined (21). Tetrachlorothiophene, a simple analog, was once a registered nematicide in the United States (43).…”
Section: Polythienyls In Tagetes Sppmentioning
confidence: 99%
“…The marigold polythienyls are only weakly nematicidal when incorporated into soil and require light or the action of peroxidase or other activators to release the singlet oxygen that kills nematodes (49,50). The details of the specific activators and processes involved in the insecticidal, nematicidal, or other toxic activities of these compounds continue to be examined (21). Tetrachlorothiophene, a simple analog, was once a registered nematicide in the United States (43).…”
Section: Polythienyls In Tagetes Sppmentioning
confidence: 99%
“…This treatment involves photo-oxidation of the relatively non-toxic IAA, which produces a compound with some degree of cytotoxicity. The use of photosensitizing dyes is typically employed in this process (Brennan et al, 2000). Our studies suggested that PN is an effective photosensitizer for IAA, and may potentially have medical applications.…”
Section: Enhancement Of Indole-3-acetic Acid Photodegradation By Vitamin B6mentioning
confidence: 78%
“…This indicates that it has a photochemistry mode and a photobiology mode in mode of action [ 37 , 38 , 39 , 40 ]. In addition, α -terthienyl can exert toxic effects when in the absence of light, and it has some activity on plants and nematodes [ 41 ]. Furthermore, Brennan reported that α -terthienyl could interfere the enzymes in Calvin cycle and inhibit photosynthetic CO 2 fixation [ 16 ].…”
Section: Discussionmentioning
confidence: 99%